Public Negotiations : Gender and Journalism in Contemporary US Latina/o Literature - Vigil, Ariana E., 1980- (Global Latin/o Americas., 2019)
""Examines how the boundaries of the Latina/o public sphere are negotiated through mass media in twentieth and twenty-first century literature, incorporating conversations regarding gender and in regards to questions of access, production, distribution, and representation"--Provided by publisher"--